2017
DOI: 10.1161/jaha.116.004541
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Extracellular RNA Reduces Edema Formation and Infarct Size and Improves Survival After Myocardial Infarction in Mice

Abstract: BackgroundFollowing myocardial infarction (MI), peri‐infarct myocardial edema formation further impairs cardiac function. Extracellular RNA (eRNA) released from injured cells strongly increases vascular permeability. This study aimed to assess the role of eRNA in MI‐induced cardiac edema formation, infarct size, cardiac function, and survival after acute MI and to evaluate the therapeutic potential of ribonuclease 1 (RNase‐1) treatment as an eRNA‐degrading intervention.Methods and ResultsC57BL/6J mice were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
(64 reference statements)
3
33
0
Order By: Relevance
“…Most notably, treatment of septic mice with RNase 1 attenuated the rise in cardiac Bax levels, activation of caspase-9 and caspase-3, the decrease in Bcl-2 and TUNEL + cells caused by sepsis in the heart (Figure 6). In line with our findings, Stieger et al reported a reduction of apoptosis 24 hours after ligation of the left anterior descending artery (LAD) in mice treated with RNase 1 (37). Treatment with RNase 1 in sham-operated mice did not show any apoptosis induction ( Figure 6).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most notably, treatment of septic mice with RNase 1 attenuated the rise in cardiac Bax levels, activation of caspase-9 and caspase-3, the decrease in Bcl-2 and TUNEL + cells caused by sepsis in the heart (Figure 6). In line with our findings, Stieger et al reported a reduction of apoptosis 24 hours after ligation of the left anterior descending artery (LAD) in mice treated with RNase 1 (37). Treatment with RNase 1 in sham-operated mice did not show any apoptosis induction ( Figure 6).…”
Section: Discussionsupporting
confidence: 91%
“…We confirm that the model of polymicrobial sepsis used here, indeed, results in a substantial cardiac dysfunction defined by a significant decrease in EF, FS, and fraction area change ( Figure 5). Stieger et al reported an increase of FS in mice treated with RNase 1 (50 μg/kg) compared with mice treated with saline 24 hours after myocardial infraction (37).We also detected a significant reduction in left ventricular cardiac dysfunction in CLP mice treated with RNase 1, as determined by a substantial increase in EF, FS, fraction area change, and cardiac output ( Figure 5). Moreover, we detected a significant reduction in the release of TNF in CLP mice treated with RNase 1 when compared with CLP mice treated with vehicle (Figure 7A).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…After 1 week, LAD ligation was performed as described earlier (Y. Cao et al, ). Briefly, mice were fully anesthetized using ketamine and xylazine (80 and 10 mg/kg, respectively; Sigma‐Aldrich, St. Louis, MO) via intraperitoneal injection (0.1 ml/10 g of body weight; Stieger et al, ). An endotracheal tube connected to a rodent respirator (Harvard Rodent Ventilator, Harvard Apparatus, Holliston, MA, USA) was introduced into the trachea.…”
Section: Methodsmentioning
confidence: 99%
“…Other forms of extracellular RNA such as microRNA have also been suggested to have a regulatory effect on collateral remodeling during arteriogenesis through modulation of intracellular signaling pathways; however, whether this effect is positive or negative seems to depend on the specific microRNA [5][6][7][8]. In terms of cardiovascular disease, eRNA released upon cellular damage has proven to have adverse effects in, e.g., ischemia/reperfusion injury, transplantation or atherosclerosis by mediating vascular edema, thrombus formation and inflammation [9][10][11][12][13][14]. This review aims to further elucidate the beneficial role of eRNA during the various stages of arteriogenesis.…”
Section: Introductionmentioning
confidence: 99%